Gambaran Perilaku Higiene Sanitasi Penjamah Makanan Pada Rumah Makan Di Kecamatan Pamulang Tangerang Selatan Tahun 2025 - Sastika, Wenda; Dadang Herdiansyah; Triana Srisantyorini; Ernyasih (ENVIRONMENTAL OCCUPATIONAL HEALTH AND SAFETY JOURNAL, 2025)
ABSTRACT In Indonesia, the main cause of death and disease is caused by food problems. Based on data from the Ministry of Health of the Republic of Indonesia, there were 4,792 cases of food poisoning in Indonesia in 2023. The main factors that often cause food contamination are poor hygiene and sanitation, both from food handlers, unsuitable eating utensils, sales locations, and food ingredients that do not meet health standards. This study is a descriptive study, namely describing the hygiene and sanitation behavior of food handlers in restaurants in Pamulang District in 2025. The study was conducted in May - June 2025 on Jalan Raya Pamulang, Pamulang District in 2025 with a sample of all food handlers totaling 54 restaurants. The results showed that respondents had poor behavior as many as 29 respondents (53.7%), respondents who had poor knowledge as many as 35 respondents (64.8%) while respondents who had poor attitudes as many as 39 respondents (53.7%). Although the respondents' attitudes regarding food handlers' hygiene are generally good, in implementing hygiene practices, there are still some respondents who do not practice hygiene properly. Therefore, food handlers must always ensure that their personal hygiene, equipment, food ingredients, and the processing environment are well maintained. Keywords: Knowledge, Attitudes, and Hygiene Behavior